Axillary Intra-aortic Balloon Pump Placement as a Means for Safe Mobility in a Patient Awaiting Left Ventricular Assist Device Implantation: A Case Report. Issue 3 (September 2015) - Shumock, Kara Marie; Appel, Jessica; Toonstra, Amy
Abstract : Introduction: Although there is no cure for heart failure, placement of an intra-aortic balloon pump (IABP) can act as temporary treatment. Historically, IABPs are inserted through the femoral artery and patients are placed on bed rest. The purpose of this case report was to demonstrate the physical therapy management of a patient with IABP catheter placement through axillary artery, including safe ambulation. Case Presentation: A 54-year-old South Asian man presented with profound cardiogenic shock. He had prolonged hospital course complicated by several femoral IABP placements, extracorporeal membrane oxygenation, and mechanical ventilation. He eventually received axillary IABP placement to allow for increased mobility. The patient was able to ambulate up to 182.88 m with a rolling walker while the axillary IABP was in place before left ventricular assist device placement, which occurred on hospital day 40. Conclusions: Physical therapy interventions, including functional mobility and gait training, were safely performed in a patient with axillary IABP access. However, additional studies are needed to support mobility as standard practice for this patient population.